Far-red LED light treatment at harvest and during storage to control sprouting in ‘Asterix’ potatoes - Pedrosa, Vanessa Maria Dantas [UNESP]; Izidoro, Maiqui [UNESP]; da Silva, Maryelle Barros; Lossolli, Nathalia Aparecida Barbosa [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP]; Carvalho, Rogério Falleiros [UNESP]; Bacha, Allan Lopes [UNESP]; de Almeida Teixeira, Gustavo Henrique [UNESP] (Elsevier, 2025)
The application of light-emitting diode (LED) light at different wavelengths has shown promising potential in reducing sprout growth in stored potatoes, where continuous exposure to high irradiance, such as far-red LED light at 5 µmol m⁻² s⁻¹ , has been shown to be most effective in suppressing sprout development. However, it may not be practical for sprout management, as potatoes are typically stored in bulk. Therefore, the objective of this study was to assess the feasibility of applying 5 µmol m−2 s−1 of far-red LED light prior to storage and to investigate the photomorphogenic and metabolic responses to these treatments throughout storage. Potato tubers of the Asterix cultivar were exposed to far-red LED light before storage (for 0, 2, or 4 min) or continuously during storage (24 h a day), and compared with untreated potatoes (control) and potatoes treated with chlorpropham (CIPC), a sprouting inhibitor. Tubers continuously exposed to far-red LED light had fewer and less developed sprouts, while the application of the pre-storage treatment for 4 min was effective for up to 55 d in storage. However, far-red LED light did not inhibit sprouting during storage. Tubers treated with far-red LED light had lower dry matter, starch, and total soluble sugar levels compared to those treated with CIPC but showed no differences in reducing sugar levels. Although promising, the far-red LED light treatment prior to storage was not fully effective in inhibiting sprouting, necessitating further studies to elucidate the mechanisms involved in tuber responses to light during storage.